Effect of catecholamines stimulation via hand cooling and the priming effect on the oxygen consumption kinetics - Louis Finiel; Fabio Borrani (Bern Open Publishing, 2024)
Introduction Priming effect has been shown to accelerate the oxygen consumption (V̇O2) kinetics. This phenomenon could be explained by muscle oxygen (O2) enhanced delivery, motor unit recruitment or intracellular O2 enhanced utilization (Goulding et al. 2023). Catecholamines such as epinephrine (E) and norepinephrine (NE) are known to impact the cardiovascular system as well as the respiratory system and metabolic effects (Zouhal et al. 2008). The aim of this study is two folds. Observing the effect of increased E and NE induced by cold-water hand immersion on V̇O2 kinetic during heavy intensity exercise bout (HCWR). Compare the effect of cold-water hand immersion and previous HCWR on V̇O2 kinetic to see if the sympathetic system could partially explain the priming effects. Methods Ten healthy active males (mean ± SD, age 23 ± 5 years, body mass 71 ± 6.5 kg) participated in this study. An incremental test was performed on ergometer to prescribe the intensity for the HCWR exercise (∆ 25%). Participants did an 8 min HCWR normal bout (NO), followed by 8 min rest and a second bout (SB) and hand cooling bout (HC) at heavy intensity in a randomized order. For the HC condition, participants put hands in cold water (0°C) for 2 min then directly did the HCWR. Blood samples has been taken at rest, before and directly after the HCWR. Results Just before exercise, all conditions were different, but HC E (1.095 ± 0.64 nmol/ml) increased by 347% while HC NE (6.98 ± 1.89 nmol/ml) matched values from SB NE (6.89 ± 2.22 nmol/ml). At the end of exercise, no significant difference has been found between NO E (1.44 ± 1.06) and HC E (1.54 ± 1.38 nmol/ml) while SB E (2.35 ± 1.55 nmol/ml) was significantly higher than both conditions but no differences have been found between HC (20.15 ± 8.76 nmol/ml) and SB (20.41 ± 9.74 nmol/ml) NE. V̇O2 kinetic has been sped up for both HC and SB by increasing the absolute primary prime amplitude of HC (33.88 ± 0.96 ml/min/kg),SB (34.60 ± 0.86ml/min/kg) compared to NO (32.75 ± 0.65 ml/min/kg) and reducing the prime amplitude of HC (3.22 ± 0.51 ml/min/kg), SB (2.90 ± 0.64 ml/min/kg) vs NO (3.87 ±0 .56 ml/min/kg) of the slow component of V̇O2. Discussion/Conclusion Catecholamines stimulation via hand cooling accelerated the V̇O2 kinetics enhancing the primary phase and reducing the slow component. This effect seemed to follow the priming effect but with less intensity. Increased O2 delivery appeared to be a common feature of both conditions, Motor neuron excitability due to increased NE was also a likely hypothesis, as both HC and SB had the same values just before exercise. Finally, intra-muscular enhancement illustrated by improved intracellular partial pressure kinetics and mitochondrial O2 utilization might explain the effects of catecholamines and part of the priming effect. Mitochondrial "warm-up" could be influenced by both catecholamines and priming effect resulting in a better production of adenosine triphosphate. References Goulding, R. P., Burnley, M., & Wüst, R. C. I. (2023). How priming exercise affects oxygen uptake kinetics: From underpinning mechanisms to endurance performance. Sports Medicine, 53, 959-976. https://doi.org/10.1007/s40279-023-01832-1 Zouhal, H., Jacob, C., Delamarche, P., & Gratas-Delamarche, A. (2008). Catecholamines and the effects of exercise, training and gender. Sports Medicine 38, 401-423. https://doi.org/10.2165/00007256-200838050-00004